ROLE OF INDIAN CONSTITUTION IN WOMEN EMPOWERMENT - Karadia, Mamta; Mehta, Sakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indian Constitution is a beautiful blend of both federal and unitary systems. The Indian Constitution is called a federal constitution on the basis that it is a written constitution. It provides for a supreme and independent judiciary. The preamble of the Indian Constitution declares the goal of making India a democratic republic. Its head of state will be elected democratically. Being a republic means that any common person of India, whether a man or a woman, can reach the highest position in the country on the basis of his qualifications. India is a union of states. It is an independent sovereign socialist democratic republic with a parliamentary system of government. This republic is governed according to the Constitution of India which was adopted by the Constituent Assembly on 26 November 1949 and which came into force on 26 January 1950. The Constitution of India is the supreme legal authority that links together the legislative, executive and judicial organs of the government. The Constitution provides fundamental rights to all citizens and gives the independent judiciary the right to declare invalid the laws or government actions that violate the Constitution. In the Vedic period, women had a very respectable position in India. But later in the medieval period, the status of women deteriorated a lot due to the arrival of foreigners. Due to illiteracy, bad customs and conservatism in the society, the status of women was greatly affected. But gradually in the first half of the nineteenth century, some social workers of India like Raja Ram Mahen Rai, Swami Dayanand Saraswati, Ishwarchand Vidyasagar and Keshavchand Sen raised their voice against the oppressive social system. They raised their voice before the then British rulers for gender equality, women education, ban on Sati Pratha and ban on polygamy, as a result of which Sati Pratha Prohibition Act, 1829 and Hindu Widow Remarriage Act in 1856, Age of Constancy Bill in 1891 and Vative Marriage Act to stop polygamy were passed. By the twenty-first century, the condition of women started improving and the Indian Constitution implemented provisions to promote women’s upliftment and empowerment and to improve their economic, social, educational and political status and to include them in the mainstream of development by running many welfare schemes and developmental works.